Game Visual Novel Edukasi Dengan Algoritma Fuzzy Mamdani - Setiawan, Jodi; Danuputri, Chyquitha; Hakim, Lukman (Universitas Mercu Buana, 2024)
Lack of interest in learning is one of the obstacles experienced by students that can affect learning power and cause students' ability to capture learning material to be hampered. Calculus is one of the subjects that is considered quite difficult due to the lack of interest in learning and the lack of basic knowledge of this course. Visual novel is a game genre that focuses on the interaction between characters and the story of the game in which it is possible for branching of stories to occur and also mini games which in this study use quizzes. Fuzzy Mamdani algorithm that can change input parameters in the form of fuzzy values into a solution can be applied to visual novels to determine the route of the story in the game. The development of the game using Multimedia Development Life Cycle (MDLC) and is made using the Unity game engine. The implementation of the fuzzy Mamdani algorithm to determine the route of the game is implemented in two parts, calculating the final value of the chapter with the parameters obtained when the user takes the quiz – the number of correct answers and processing time to determine the storyline at the end of the chapter – and determination of the final value of the game – using parameters of the average value of chapter result and accumulation of additional questions that can be answered correctly by the user. The comapred results between manual and program calculation shows the same result.